PEMIMPIN NON-MUSLIM DALAM PERSPEKTIF IBNU TAIMIYAH - Khalik, Abu Tholib (Universitas Islam Negeri Raden Intan Lampung, 2014)
THE APPOINTMENT A NON-MUSLIM LEADER IN PERSPECTIVE OF IBN TAYMIYYAH. Controversy on the appointment of a non-Muslim leader among the majority of Muslims emerges frequently. Historically, the issue has been going on for a long time and always invites debates among the Muslim scholars from time to time. In response to this issue, the scholars are divided into two camps, most of them forbid it but others allow. One of the scholars allowing the appointment was Ibn Taymiyyah, a great Islamic thinker of his time. He was famous of his controversial statement “better led by a fair pagan than led by a tyrannical Muslim leader”. This article illustrates the relevance of “liberal” thought of Ibn Taymiyyah on the administration of state, especially on the issue of the non-Muslim leadership in the middle of the vast majority of Muslims. This view is quite relevant to address the uncertainty of the majority of Muslims who are hostile to each other in choosing a candidate while the proposed candidate does not deserve to be a leader.